The Semantic Change in The Interpretation of Al-Qurtubi - Nada Sami Naser (QALAAI ZANIST JOURNAL, 2022)
This research is concerned with the phenomenon of semantic change, which is one of the phenomena of semantic development that modern linguists have been interested in a lot by showing it to the ancient Arab linguists, especially the exegetes of the Holy Qur’an, including Al-Qurtubi, who is the field of this research. The semantic one was (the semantic change in terms of specifying or expanding the meaning), which is that the general connotation is limited to some of its parts and its comprehensiveness is narrowed so that the meaning of the word becomes limited to things that are less in number than what the word was originally. From the defining points of this change through branches distributed between the allocation of meaning, the generalization of significance, and the change of the field of significance (transfer of meaning), putting our hands through it on some aspects of the semantic development of Al-Qurtubi, hoping that researchers in this field will benefit from it.